On exemption from administrative liability in case of a minor administrative offense - B. Yu. Jamirze (Гуманитарные и юридические исследования)
Introduction. A number of specific issues are central to modern national practice of application of legislation on administrative. It is preconditioned by constant improvement of legislation, which is carried out to effectively counter internal and external challenges to the Russian state and society. The principle of justice retains its paramount importance, determining the status of the mechanism of administrative responsibility precisely as a means of public administration. The peculiarities of the practical implementation of this principle are expressed, among other things, in the institution of exemption from administrative liability, one of the grounds of which is the insignificance of an administrative offense - an evaluative category that is significant for the practice of applying legislation on administrative offenses. Materials and methods. The study is based on the analysis of provisions of the current legislation on administrative liability, materials from relevant judicial practice and the work of researchers on this issue. Analysis. The provisions of the current legislation and rulings of higher courts containing explanations of these provisions do not provide a comprehensive picture of the specifics of the application of the rules on the insignificance of an administrative offense, including the relevant categories of cases and the subject composition. Results. Based on the results of the study, we can conclude that the rules on exemption from administrative liability in the event of a minor administrative offense require additional clarification from the Supreme Court of the Russian Federation to determine the categories of violations to which these rules apply, as well as the range of subjects to which they apply. The author's position on possible answers to the questions posed is formulated.